Effect of plant population on yield of maize and climbing beans grown in an intercropping system - Niringiye, C.; Ssekabembe, CS; Kyamanywa, S. (2005)
Increased adoption of climbing beans ( Phaseolus vulgaris check for this species in other resources L.) in Kabale district, south-western Uganda, has been limited by scarcity of staking materials, despite the crop's higher yield potential compared to bush bean types when grown on fertile soils. There is therefore need to explore other appropriate mechanisms such as intecropping, that could substitute use of stalks. A field experiment was conducted at Kachwekano near Kabale town for two seasons: second rains of 1996 (1996b) and first rains of 1997 (1997a), to determine the appropriate plant population density (PPD) of maize that would maximize bean yield in an intercrop system. The treatments were: (a) maize PPD ranging from 25 000 to 40 000 plants ha-1, and (b) bean PPD ranging from 57 142 to 95 238 plants ha-1. Sole crops were planted at the recommended PPD of 44 444 and 111 111 plants ha-1 for maize and climbing beans, respectively. Maize in mixtures was planted in single rows 1.0 m apart. Two rows of beans were planted in the space between maize rows, 10 days after maize emergence. Plant densities were achieved by varying the within-row spacing from 0.25 to 0.40 m for maize and 0.30 to 0.50 m for beans. Maize PPD significantly affected bean yield only during the second rains (1996b), probably due to a favourable moisture regime. Bean PPD significantly affected maize yield only during the first rains (1997a), presumably due to drought stress. The highest intercrop bean yield of 1.075 t ha-1 was realised from a final mixture of 24 575 and 66 666 plants ha-1 of maize and beans, respectively, during the second rains. Intercropping significantly reduced maize yield during the second rains and bean yields in both seasons. The intercrop system had a yield advantage of 26 % (i.e., LER = 1.26) over pure stands of the component crops only during the second rains, presumably due to complementary use of resources. However, there were no yield advantages observed during the first rains probably due to drought stress. Mean total income (TI) from the mixtures was 226.8 and 31.8% higher than income from sole bean and maize crops, respectively, during the second rains. Income from the mixtures was 58.7 and 72.5 % higher than income from sole bean and maize crops, respectively, during the first rains.